Study of inside-out technique of trans-obturator tape for treatment of stress urinary incontinence in women with utero-vaginal prolapse - Verma, Ragini (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Assessment of the success rates and complications of inside-out technique of Trans-Vaginal Tape (Obturator) (TVT-O) for treatment of stress urinary incontinence (SUI) in women with utero-vaginal prolapse. MATERIALS AND METHODS: A total of 30 consenting subjects with SUI and utero-vaginal prolapse were subjected to TVT-O surgery. These subjects were closely monitored for complications and success rate of surgery up to 1 year of surgery. RESULTS: Urinary tract infection (16.67%) was the most common early post-operative complication. Groin pain (23%) was the most common late post-operative complication while denovo urgency developed in 3 (11.54%) subjects. Majority (88.46%) of subjects had total improvement at 3month follow-up while 100% subjects had total improvement at 12 month follow-up with a “definitely improved quality-of-life.” CONCLUSION: The TVT-O (inside-out) appears to have performed favorably as a safe and effective surgery for SUI associated with utero-vaginal prolapse.